2016
DOI: 10.1038/srep21939
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Conformational dynamics is key to understanding loss-of-function of NQO1 cancer-associated polymorphisms and its correction by pharmacological ligands

Abstract: In addition, the 'How to cite this article' section quoted an incorrect abbreviation for Encarnación Medina-Carmona. These errors have now been corrected in the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mutational effects on FAD binding affinity (ΔΔG FAD ) and proteolysis rates (ΔΔG PROT ) with thermolysin have previously been shown to correlate well ( Medina-Carmona et al, 2017a ; Medina-Carmona et al, 2019b ; Pacheco-García et al, 2020 ). The site for initial cleavage by thermolysin (TCS) is generally between Ser72–Val73, close to the FAD binding site ( Medina-Carmona et al, 2016 ). All the variants investigated showed proteolysis patterns that were similar to that of WT NQO1 ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational effects on FAD binding affinity (ΔΔG FAD ) and proteolysis rates (ΔΔG PROT ) with thermolysin have previously been shown to correlate well ( Medina-Carmona et al, 2017a ; Medina-Carmona et al, 2019b ; Pacheco-García et al, 2020 ). The site for initial cleavage by thermolysin (TCS) is generally between Ser72–Val73, close to the FAD binding site ( Medina-Carmona et al, 2016 ). All the variants investigated showed proteolysis patterns that were similar to that of WT NQO1 ( Supplementary Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that ligand binding and variant effects on stability propagate to long distances in the native state, affecting different functional features in a counterintuitive fashion ( Medina-Carmona et al, 2016 ; Pey, 2018 ; Medina-Carmona et al, 2019a ; Vankova et al, 2019 ; Pacheco-García et al, 2020 ; Pacheco-Garcia et al, 2021 ; Pacheco-Garcia et al, 2022a ). Therefore, NQO1 represents a challenging and biomedically relevant system to compare the performance of computational and experimental methods to explain and to predict genotype-phenotype in a large-scale for a multi-functional protein.…”
Section: Introductionmentioning
confidence: 99%